PENYULUHAN DAN PEMERIKSAAN KADAR HEMOGLOBIN SEBAGAI SALAH SATU UPAYA DETEKSI DINI ANEMIA PADA IBU HAMIL: Counseling - Hardaniyati Hardaniyati; Irni Setyawati; Dian Soekmawaty Riezqy Ariendha; Yesvi Zulfiana (Jurnal LENTERA, 2022)
The high prevalence of anemia has negative consequences such as the firstdisturbance and inhibition of growth, both body cells and brain cells, while thesecond deficiency of Hb in the blood results in a lack of oxygen beingcarried/transferred to body cells and to the brain. The incidence of anemia inpregnant women in Indonesia is still high, namely 37.1, the prevalence ofanemia in pregnant women in Indonesia is 37.1%. cases of anemia in pregnant women have increased every year, namely in 2015 at the Sengkol HealthCenter as many as 200 cases, and in 2016 as many as 251 cases. Hemoglobinlevels as an early detection of anemia in pregnant women.His communityservice partner is the Chair of STIKes Yarsi Mataram and the Head of theMidwifery Study Program for the Bachelor program. This service to thecommunity uses the method of counseling and checking the hemoglobin ofpregnantwomen using the "easy touch" Hb meter. The results obtained fromthis service were the examination of 30 pregnant women in two polindes areasof the Sengkol Public Health Center, namely Tanak Awu Village and KetareVillage. From all participants, the average Hb level was 10.5 g/dL, the averageage of pregnant women was 20 years. The participants felt that this activity wasvery beneficial for them for the health of themselves and their fetus. Participantsalso hope that this community service activity can be carried out regularly